Long-term adaptive response in COVID-19 vaccine recipients and the effect of a booster dose - Perico, Luca; Todeschini, Marta; Casiraghi, Federica; Mister, Marilena; Pezzotta, Anna; Peracchi, Tobia; Tomasoni, Susanna; Trionfini, Piera; Benigni, Ariela; Remuzzi, Giuseppe (Frontiers in Immunology, 2023)
We examined the immunoresponse in subjects previously infected with SARS-CoV2 and infection-naïve 9 months after primary 2-dose COVID-19 mRNA vaccination and 3 months after the booster dose in a longitudinal cohort of healthcare workers. Nine months after primary vaccination, previously infected subjects exhibited higher residual antibody levels, with significant neutralizing activity against distinct variants compared to infection-naïve subjects. The higher humoral response was associated with higher levels of receptor binding domain (RBD)-specific IgG+ and IgA+ memory B cells. The booster dose increased neither neutralizing activity, nor the B and T cell frequencies. Conversely, infection-naïve subjects needed the booster to achieve comparable levels of neutralizing antibodies as those found in previously infected subjects after primary vaccination. The neutralizing titer correlated with anti-RBD IFNγ producing T cells, in the face of sustained B cell response. Notably, pre-pandemic samples showed high Omicron cross-reactivity. These data show the importance of the booster dose in reinforcing immunological memory and increasing circulating antibodies in infection-naïve subjects.